Faktor Yang Berhubungan Dengan Keluhan Cumulative Trauma Disorders (CTDs) Pada Buruh Angkut Di Kantor Koperasi Tenaga Kerja Bongkar Muat (KTKBM) Pelabuhan Kota Makassar - Mutmainnah, Ainun; Alfina Baharuddin; Sulaeman, Ulfa (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
According to data from the International Labor Organization (ILO), in 2013, 1 worker in the world died every 15 seconds due to work accidents, and 160 workers suffered from work-related illnesses. The Indonesian Ministry of Health on the Profile of Workers' Health Problems in Indonesia in 2005 found that 40.5% of workers complained of disorders related to their health, namely 16% musculoskeletal diseases, 8% cardiovascular, 6% nerve disorders, 3% respiratory diseases, 1.5% ENT disorders, and 1.3% skin disorders. The type of research used is quantitative research with a cross-sectional study approach designed to determine the Factors Related to Cumulative Trauma Disorders (CTDs) Complaints in Port Workers at the Office of the Stevedores' Cooperative (KTKBM) of Makassar City Port. The results of this study indicate that out of 83 respondents at the Office of the Stevedores' Cooperative (KTKBM), there is a relationship between age in port workers and Cumulative Trauma Disorders (CTDs), which obtained a p-value = 0.000 <0.005. There is a relationship between length of service in port workers and Cumulative Trauma Disorders (CTDs), which obtained a p value = 0.000 <0.005. There is a relationship between workload in porters and Cumulative Trauma Disorders (CTDs), which obtained a p value = 0.000 <0.005 and there is no relationship between body mass index in porters and Cumulative Trauma Disorders (CTDs), which obtained a p value = 0.473 >0.005. Based on the results of the study, discussion, and conclusions, the suggestion that the researcher conveys is for porters to use their rest time as much as possible and exercise diligently to stretch their muscles.